2014
DOI: 10.1039/c3ee43289k
|View full text |Cite
|
Sign up to set email alerts
|

Gold-plasmon enhanced solar-to-hydrogen conversion on the {001} facets of anatase TiO2 nanosheets

Abstract: A 64-fold improved efficiency of solar-to-hydrogen conversion (SHC) was achieved via exposing Au nanoparticles (NPs) on the {001} facets of anatase TiO 2 nanosheets. The SHC follows a surface plasmon resonance-mediated electron injection mechanism, where Au NPs can not only harvest visible light and convert them to free energetic electrons, but promote the SHC by increasing the electron-hole pair formation rate driven by the electromagnetic field formed nearby the semiconductor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 42 publications
4
121
1
Order By: Relevance
“…However, the dopants can easily become the recombination centers for charge carriers and lower stability of the doped materials. Deposition of transition or noble metals onto T001 is an effectively strategy to enhance visible light photocatalytic activity [15][16][17][18][19][20]. Nevertheless, metal clusters at a higher concentration will also serve as a recombination center for electron-hole pairs, which noticeably decreases the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 98%
“…However, the dopants can easily become the recombination centers for charge carriers and lower stability of the doped materials. Deposition of transition or noble metals onto T001 is an effectively strategy to enhance visible light photocatalytic activity [15][16][17][18][19][20]. Nevertheless, metal clusters at a higher concentration will also serve as a recombination center for electron-hole pairs, which noticeably decreases the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 98%
“…Priebe et al furthermore correlated the ESR signal intensities of conduction band electrons at O vacancies of Au/P25 with the irradiation wavelength and showed a matching response to the LSPR of Au [134]. Long et al tracked the ESR signal intensity of Ti 3+ -surface states for Au/TiO 2 (anatase nanosheets) under visible light irradiation and also assigned their results to an electron injection mechanism [38]. The previous examples with Au and TiO 2 demonstrate the concept of DET.…”
Section: Direct Electron Transfermentioning
confidence: 91%
“…Long et al showed a poor match between the LSPR absorption of Au NPs on TiO 2 and photoelectrochemical measurements [38]. It was concluded that only high energy charge carriers excited at around 420 nm were able to migrate to TiO 2 .…”
Section: Direct Electron Transfermentioning
confidence: 97%
“…Nowadays, many strategies have been developed to address the above problems for TiO 2 in the field of photocatalysis, such as heteroatoms doping [13][14][15][16][17][18][19][20], coupled with other semiconductors [21][22][23][24][25][26][27], dye-sensitization [28][29][30], and precious metal deposition [31][32][33][34][35][36][37][38]. Previous studies have shown that heteroatoms doping has proved to be an effective way to generate the impurity levels in the wide band of TiO 2 , which can effectively make the TiO 2 active in the visible region and restrain the recombination rate of photoinduced electrons and holes [1,39].…”
Section: Introductionmentioning
confidence: 99%